2013
DOI: 10.3109/13625187.2013.772974
|View full text |Cite
|
Sign up to set email alerts
|

Female undergraduate fine arts students: A high-risk population for multiple sexual partners, unwanted pregnancy and sexually transmitted infections in China

Abstract: Female fine arts students hold more tolerant attitudes toward sex than other female students. They were more inclined to risky sexual behaviours, and thus more vulnerable to unwanted pregnancy and STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is notable that vocational college students, as well as arts and sports students were not included in our study. One study reported a prevalence of sexual intercourse among female arts university students as high as 35% [ 18 ]. A meta-analysis might be helpful to determine the exact prevalence of sexual intercourse in unmarried female students.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that vocational college students, as well as arts and sports students were not included in our study. One study reported a prevalence of sexual intercourse among female arts university students as high as 35% [ 18 ]. A meta-analysis might be helpful to determine the exact prevalence of sexual intercourse in unmarried female students.…”
Section: Discussionmentioning
confidence: 99%
“…A liberal attitude towards sex, motives for risky behaviours, current cigarette smoking and problematic alcohol consumption were all found to be associated with ever having sexual activity. A liberal attitude towards sex is known to increase risky sexual activity (Zou et al, 2013), with subsequent vulnerability to unwanted pregnancies and sexually transmitted diseases. An association of risky sexual behaviour with substance and alcohol abuse has also been demonstrated (O'Hare, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Youth have been identified as the population group that is the most vulnerable to unwanted pregnancy, HIV infections and STIs. A study on 4769 female undergraduates reported that 18% of the students had previously had sex and that the proportions of students with self-reported pregnancies and STIs were 17.5 and 20.4%, respectively [7]. A cross-sectional study including university students from 49 universities across 7 cities in China indicated that approximately one-third of unmarried female university students engaging in sexual intercourse had experienced unintended pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%